Pengembangan Game Edukatif Berbasis Budaya Betawi (Geduk Babe) Untuk Meningkatkan Kemampuan Mengenal Bentuk Geometri - Azkia, Hilwa; Risma, Devi; N, Zulkifli (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2025)
This research aims to develop GEduk BaBe (Educative Game Based on Betawi Culture) to improve the ability to recognize geometric shapes for children aged 5-6 years. The type of research used is research and development. The steps taken are : are analysis which aims to identify the needs to develop GEduk BaBe, the design stage which is preparing the initial product design for GEduk BaBe, the development stage which is integrating the technology that will be used by producing media products that are validated by experts, the implementation stage which is conducting a trial of the GEduk BaBe product to ensure it functions properly (practically) or not and finally the evaluation stage to determine the effectiveness of the GEduk BaBe media. Data collection techniques using observation, questionnaires and LKA. The instrument used was a questionnaire for validation of GEduk BaBe from media experts, material experts and educators. The data analysis technique used is quantitative descriptive analysis technique. In the research, media expert validation was obtained at 90.63% "Very Appropriate", material expert validation was 93.75% "Very Appropriate", and educator validation obtained a percentage result of 86.88% "Very Appropriate". The results of the pretest assessment obtained a percentage result of 36.20% and the results of the posttest assessment showed an increase in the percentage result of 79.43%. From the research results, it was concluded that GEduk BaBe (Educative Game Based on Betawi Culture) is suitable for use as a learning medium in improving the ability to recognize geometric shapes in children aged 5-6 years at RA Ar-Ridwan, South Jakarta.